Designing the metaverse: A study on inclusion, diversity, equity, accessibility and safety for digital immersive environments. (December 2022) - Zallio, Matteo; Clarkson, P. John
Highlights: The Metaverse appears as the next big opportunity in the consumer electronics scenario. There are currently several companies involved with its development. It is extremely important to define principles and practices to design a good Metaverse. Qualitative research pointed out to challenges and opportunities to design a safe, inclusive, accessible Metaverse that guarantees equity and diversity. Ten principles for designing a good Metaverse embrace inclusion, diversity, equity, accessibility and safety. Abstract: The metaverse, a digital immersive environment in which people interact by using immersive technologies, is shaping a new way for people to interact and socialise. Forecasts predict that by 2026 a quarter of the population will spend at least an hour a day in the metaverse. This projection requires the consideration of several challenges and opportunities that will influence the design of the metaverse. A qualitative ethnographic study with industry experts was carried out to explore the social impact of the metaverse through the lens of inclusion, diversity, equity, accessibility and safety with the goal to identify directions business have to undertake. The results indicated the vast nature of future research questions that will need to be answered and facilitated the creation of good practices for designing an inclusive, accessible, safe metaverse that guarantees equity and diversity. These good practices are a starting point to develop a narrative, spark conversations, brainstorm questions and eventually provide answers for designing a metaverse as a place for people that does not substitute the physical world but complements it.